Sustainable manufacturing framework from Islamic perspective - Zain, Saidi; Adesta, Erry Yulian Triblas; Ismail, Ahmad Faris; Ahmad, Zuraida (IOP Publishing, 2016)
Islam is a complete way of life and offers holistic and comprehensive solutions to the human life. Manufacturing is one of the fields in which the voice of Islam is hardly heard. The efforts to relate and integrate manufacturing practices with Islamic principles and to eventually create a holistic solution is still lacking. This study is an attempt to develop a framework of sustainable manufacturing practices from the Islamic perspective. This framework may offer optional solutions to the current problems faced by the world such as global warming, climate change, pollutions, diseases etc. due to human ignorance. The framework was developed based on a preliminary research on the recent study of Maqasid Shari’ah, which is used as the main foundation. The developed framework comprises of three main domains, namely social, economic and environment. The framework is hoped to offer alternative solutions in producing high quality products, whilst taking into consideration the society, economy and environment, in line with the teachings of Islam and in accordance to our subservience to Allah SWT